2002
DOI: 10.1097/00042560-200203010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Maternal Outcome After Administration of Tenofovir to Gravid Rhesus Monkeys (Macaca mulatta)

Abstract: Tenofovir has been shown to cross the placenta in quantities sufficient to sustain reductions in viral load in simian immunodeficiency virus (SIV)-infected fetal monkeys. With chronic exposure (30 mg/kg), however, significant bone-related toxicity has been shown in approximately 25% of infants studied. Further investigations were conducted to determine whether the bone-related toxicity observed was initiated during fetal life. Gravid rhesus monkeys (n = 4) were administered tenofovir subcutaneously once daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 52 publications
2
47
1
Order By: Relevance
“…80 In studies on gravid rhesus monkeys administered tenofovir subcutaneously once daily from 20 to 150 days of gestation, there was normal fetal development, although overall body weights and crown-rump lengths were less than those fro age matched controls, along with a small reduction in fetal bone porosity. 81,82 Tenofovir is a pregnancy category B medication. It has been safely used in pregnant women with HIV (some with HBV co-infection).…”
Section: Tenofovirmentioning
confidence: 99%
See 1 more Smart Citation
“…80 In studies on gravid rhesus monkeys administered tenofovir subcutaneously once daily from 20 to 150 days of gestation, there was normal fetal development, although overall body weights and crown-rump lengths were less than those fro age matched controls, along with a small reduction in fetal bone porosity. 81,82 Tenofovir is a pregnancy category B medication. It has been safely used in pregnant women with HIV (some with HBV co-infection).…”
Section: Tenofovirmentioning
confidence: 99%
“…These concerns first arose from studies showing that high doses of tenofovir given to pregnant rhesus macaques caused bone demineralization, impaired somatic growth, and low levels of insulin-like growth factor-1 in their infants. 81,82 Renal tubular leak of phosphate resulted in bone demineralization and deformities in macaque infants given high dose tenofovir, although these effects were largely reversible once tenofovir was stopped. 83 Despite increasing numbers of infants being exposed to tenofovir in utero and use of off-label tenofovir in HIV-infected children, data on its effects on renal function, bone mineralization, and growth remain relatively sparse; in particular, few studies have included a control group.…”
Section: Tenofovirmentioning
confidence: 99%
“…Animal 29046 had been on a high-dose PMPA regimen (30 mg/kg per day subcutaneously) since birth, but the daily dose was reduced to 10 mg/kg at 25 months of age and to 5 mg/kg at 78 months of age (Table 2); 24-h urine collections were performed for animal 29046 at 66 (circle), 75 (square), and 90 (triangle) months of age. 45, and 54 months of age), urine was collected over a 24-h period from these two animals treated with a low dose and analyzed, and the results were compared to those for untreated age-matched animals. The different parameters related to urinary excretion of phosphorus, calcium, and potassium in the two PMPA-treated animals were in the upper portion of the range or were slightly above the range for the untreated animals at some of the time points, but there was considerable variability within each animal and over time; there is no evidence to suggest that this loss of elements by urinary excretion in the PMPA-treated animals increased over time (Fig.…”
Section: Vol 48 2004 Safety Of Pmpa (Tenofovir) In Macaques 1475mentioning
confidence: 99%
“…At that time, a dosage reduction to 2.5 mg/kg per day subcutaneously again resulted in improvements in these markers. In contrast, female animal 31122 was maintained on the daily subcutaneous 10-mg/kg regimen dosage for more than 5 years; glucosuria was never detected, while serum phosphorus levels were normal, with the exception of a transient decrease to levels of ϳ3 to 4 mg/dl during pregnancy (see below), which is also seen in untreated pregnant animals and which was therefore considered physiologic (45); serum creatinine levels for animal 31122 remained low (Ͻ0.8 mg/dl).…”
Section: Vol 48 2004 Safety Of Pmpa (Tenofovir) In Macaques 1475mentioning
confidence: 99%
“…There is evidence that antiretroviral drugs such as Lamivudine, Tenofovir, and Telbivudine can prevent vertical transmission when administered to women with a high HBV viral load in the third trimester (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). It has been reported that mothers who have a viral load more than HBV DNA levels ≥ 10 6 copies/mL are at greatest risk for the transmission of the HBV to their infants.…”
Section: For a Pregnant Woman With A Positive Hbsag Test In Her Prenamentioning
confidence: 99%